Phronesis at the Human-Earth Nexus: Managed Retreat - Bohle, Martin; Marone, Eduardo (Frontiers in Political Science, 2022)
This study explores how experiences from the current pandemic can inform societal responses to future climate change. To that end, an established philosophical concept of geoscientific insights (geoethics) is utilized to advice on governance under systemic uncertainty that, in turn, is a critical feature of complex-adaptive dynamics. Illustrative examples are the Covid-19 health pandemic and the impact of the global sea-level rise to threatening heights in the early 22nd Century. The term “geoethics” labels an emergent geo-philosophical school of thought rooted in geoscience expertise. When combined with contemporary political philosophies, geoethics leads to a geo-philosophical framework that can support adaptation to complex-adaptive dynamics by favoring multi-agent and context-depending processes (e.g., learning-by-doing). The proposed geo-philosophical framework merges geoethics with the political philosophies of H. Jonas (1903–1993), L. Kohlberg (1927–1987), and M. Bunge (1919–2020). These contemporary philosophies emphasize as relevant for achieving a modern caretaking society, respectively, “the hierarchy of societal coordination processes,” “the intergenerational responsibility of agents of change,” and “the balancing of individual wellbeing (happiness) and duties.” When these philosophies are combined with geoethics, a logical approach can be derived for policy design and decision-making. It emphasizes the “autonomy” (of the human agent) combined with a civic culture that favors “trustworthiness,” “scientific culture.” and a “culture of inclusive justice.” We argue that governance of adaptation to complex-adaptive dynamics (e.g., climate change impact) can be informed by the geo- and society-centric perspectives of the proposed geo-philosophical framework. It can address “Human Earth Nexus” governance issues using the knowledge of both natural and social sciences and applying the lens of geoethical thinking.